HUBUNGAN ANTARA TIPE KEPRIBADIAN A-B TERHADAP PERILAKU MEROKOK - Aris Setiawan (Ilmu Psikologi Universitas Yudharta Pasuruan)
Smoking has become one of the habits of Indonesian people, although most of them already know the dangers of smoking. Cigarette smoke contains 4000 dangerous chemicals, while consequence of tobacco burning will cause toxins and carcinogens that can trigger cancer. Personality type is one of the factors related to smoking behavior, A personality type has characteristics: impatient, work oriented, stubborn and like to compete, while personality type B has the following characteristics: patient, not work oriented, relaxed and don't like to compete.The purpose of this research is to find out, there is a relations between the tendency of A-B personality types with smoking behavior. The population in this study were male students, which is active in the University of Yuharta Pasuruan. Academic year 2006-2007 and using accidental sampling technique, and there are 92 students.the information using observation and interview methods and the analysis using one predictor regulation, where the proxy is 0.1469697 with a r table of 5% of 2.207 and an F count of 1.9869259 with an F table of 5% of 3.93, thus both personality type A and personality type B. Both show high smoking behavior and some show low smoking behavior, so that personality types do not affect smoking behavior.